2003
DOI: 10.1039/b305623f
|View full text |Cite
|
Sign up to set email alerts
|

SuperQuat N-acyl-5,5-dimethyloxazolidin-2-ones for the asymmetric synthesis of α-alkyl and β-alkyl aldehydes

Abstract: The proclivity of alpha-branched N-2'-benzyl-3'-phenylpropionyl derivatives of (S)-4-benzyl-5,5-dimethyl-, (S)-4-phenyl-5,5-dimethyl-, (S)-4-isopropyl-5,5-dimethyl-, (S)-4-benzyl- and (S)-4-benzyl-5,5-diphenyl-oxazolidin-2-ones to generate directly 2-benzyl-3-phenylpropionaldehyde upon hydride reduction with DIBAL is investigated. The (S)-4-benzyl-5,5-dimethyl-derivative proved optimal for inhibition of endocyclic nucleophilic attack, giving 2-benzyl-3-phenylpropionaldehyde in good yield upon reduction. Applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…The diastereomeric ratio, 96% dr, was determined by GCMS, and it was increased up to 99% by recrystallization of 60 from EtOH. The cleavage of chiral auxiliary of 60 by reduction with DIBAL afforded the alkynyl aldehyde 61 in 96% yield, 52 Then, we examined the preparation of the target molecules 56 and 57 from the diyne segment 63 and the naphthalene part of 58 as depicted in Scheme 19. The bromonaphthoquinone 64 was prepared from 1,5-dihydronaphthalene in four steps in 74% yield by the known procedure.…”
Section: Scheme 17mentioning
confidence: 99%
See 1 more Smart Citation
“…The diastereomeric ratio, 96% dr, was determined by GCMS, and it was increased up to 99% by recrystallization of 60 from EtOH. The cleavage of chiral auxiliary of 60 by reduction with DIBAL afforded the alkynyl aldehyde 61 in 96% yield, 52 Then, we examined the preparation of the target molecules 56 and 57 from the diyne segment 63 and the naphthalene part of 58 as depicted in Scheme 19. The bromonaphthoquinone 64 was prepared from 1,5-dihydronaphthalene in four steps in 74% yield by the known procedure.…”
Section: Scheme 17mentioning
confidence: 99%
“…The diastereomeric ratio, 96% dr, was determined by GCMS, and it was increased up to 99% by recrystallization of 60 from EtOH. The cleavage of chiral auxiliary of 60 by reduction with DIBAL afforded the alkynyl aldehyde 61 in 96% yield, 52 which was converted into the 1,6-heptadiyne derivative 62 in 71% yield using the Corey-Fuchs method. Treatment of 62 with BuLi, followed by addition of Bu Then, we examined the preparation of the target molecules 56 and 57 from the diyne segment 63 and the naphthalene part of 58 as depicted in Scheme 19.…”
Section: Scheme 15mentioning
confidence: 99%
“…We demonstrated that the conjugate additions of organocopper reagents to an α,β-unsaturated Nacyl L-Phg-SuperQuat derivatives 88 proceed with very high diastereoselectively to give the corresponding β-functionalised products. 6,7,33 In contrast to the use of derivatives of L-Phg-SuperQuat 25, use of L-Val-SuperQuat 23 or L-Phe-SuperQuat 24 in this reaction manifold results in significantly poorer levels of diastereoselectivity. 6 A similar trend is noted using the analogous N-acyl Evans auxiliaries 34 although the reasons for this disparity are unclear.…”
Section: Stereoinduction At the β-Carbonmentioning
confidence: 99%
“…121- 125 A limited number of literature reports describe the successful direct conversion of N-acyl oxazolidin-2-ones derived from the Evans auxiliary 70 to the corresponding aldehydes, [126][127][128][129][130][131][132][133][134] although in general this transformation suffers from competing endocyclic cleavage. 135 Accordingly, a two step approach involving either reduction to the corresponding alcohol followed by chemoselective oxidation 136 or transamidation of the N-acyl oxazolidin-2-ones to the corresponding Weinreb amide followed by reduction with DIBAL-H or LiAlH 4 are employed to obtain the desired enantiopure aldehydes. As a solution to this problem, we developed the analogous series of 4-substituted-5,5-dimethyl oxazolidin-2-ones ''SuperQuats'' 71.…”
Section: Trans-fox Chiral Auxiliarymentioning
confidence: 99%